TRANSPARENT TESTA GLABRA 1-Dependent Regulation of Flavonoid Biosynthesis - Zhang, Bipei (Plants (Basel), 2017)
The flavonoid composition of various tissues throughout plant development is of biological relevance and particular interest for breeding. Arabidopsis thaliana TRANSPARENT TESTA GLABRA 1 (AtTTG1) is an essential regulator of late structural genes in flavonoid biosynthesis. Here, we provide a review of the regulation of the pathway’s core enzymes through AtTTG1-containing R2R3-MYELOBLASTOSIS-basic HELIX-LOOP-HELIX-WD40 repeat (MBW(AtTTG1)) complexes embedded in an evolutionary context. We present a comprehensive collection of A. thaliana ttg1 mutants and AtTTG1 orthologs. A plethora of MBW(AtTTG1) mechanisms in regulating the five major TTG1-dependent traits is highlighted.